Behavioral and emotional difficulties and HIV treatment outcomes among HIV-infected children in rural southwestern China - Yesheng Zhou; Kailing Tang; Hongyan Lu; Hongli Chen; Haomin Xie; Zeyu Li; Jinghua Huang; Ningye Fang; Siya Chen; Hong Wang; Qin He; Huanhuan Chen; et al. (BMC, 2023)
Abstract Background Previous studies have not clearly demonstrated the impact of behavioral and emotional problems (BEDs) on treatment outcomes among HIV-infected children on antiretroviral therapy (ART). This study aimed to describe the prevalence of BEDs among this population and identify the factors associated with HIV treatment outcomes. Methods This cross-sectional study was conducted in Guangxi, China, between July and August 2021. HIV-infected children answered questionnaires about BEDs, physical health, social support, and whether they have missed doses in the past month. BEDs were assessed using the Chinese version of the self-reported Strengths and Difficulties Questionnaire (SDQ-C). The self-reported survey data were linked to participants' HIV care information that was obtained from the national surveillance database. Univariate and multivariate logistic regression models were used to identify factors that were associated with missed doses in the past month and virological failure. Results The study sample was 325 HIV-infected children. HIV-infected children had a higher proportion of abnormal scores on SDQ-C total difficulties compared to their peers in the general population (16.9 vs 10.0%; P = 0.002). An abnormal SDQ-C total difficulties score (AOR = 2.06, 95%CI: 1.10-3.88) and infrequency of receiving assistance and support from parents over the past 3 months (AOR = 1.85, 95%CI: 1.12-3.06) were significantly associated with missed doses in the past month. Between the ages of 14-17 years (AOR = 2.66, 95% CI: 1.37-5.16), female (AOR = 2.21, 95% CI: 1.20-4.08), and suboptimal adherence (AOR = 2.45, 95% CI: 1.32-4.57) were significantly associated with virological failure. Conclusions Children's mental health plays a role in HIV treatment outcomes. Psychological interventions should be promoted in pediatric HIV care clinics to improve children's mental health status and HIV treatment outcomes.